EMPLOYEE DISCIPLINE AND ATTITUDE TO JOB SATISFACTION IN SEKRETARIAT DAERAH KABUPATEN MINAHASA - Demak, Jihan Rizki Kiay; Pangemanan, Sifrid S (Universitas Sam Ratulangi, 2014)
The society requires the work of government apparatus who are able to give serious attention in optimalize public service well. Experience and observation of Indonesian bureaucracy history along this time is not showing prime condition as the society expectation.This condition is the main factor that the core problem of the unsuccesful inefficiency of the bureaucracy work in order to go to bureaucracy in good governance.The matter of work satisfaction in relation with discipline and working attitude becoming essential since at last all of that will influenced the institution’s ability in reaching the goals. The purpose of this research is to analyze influence of employee discipline and attitude towards employee job satisfaction and to identify which factors that have the most significant influence to the employee job satisfaction. The research method that used in this research associative with multiple linear regression analysis technique, as sample of the research 58 respondent taken from employees at Sekretariat Daerah of Minahasa regency. The finding revealed that both employee discipline and employee attitude have significant effect to the job satisfaction of SEKDA Minahasa. They should apply the discipline sanction objectively and feel free in carrying on their aspiration. Keywords: employee discipline, employee attitude, job satisfaction.